The Relationship Between Achievement Motivation and Academic Flow in Middle School Students of Muhammadiyah 8 Tanggulangin Sidoarjo during the Covid-19 Pandemic - Wahyu Dewi Ningtyas; Dwi Nastiti (Journal of Islamic and Muhammadiyah Studies, 2022)
This study aims to determine the relationship between achievement motivation and academic flow in students of Muhammadiyah Junior High School 8 Tanggulangin Sidoarjo during the Covid-19 pandemic. Academic flow is influenced by several factors, one of which is achievement motivation. This type of research is quantitative research with a correlational approach. The variables in this study are achievement motivation as the independent variable and academic flow as the dependent variable. The population in this study were 174 students. The sampling technique used is a non-probability sampling technique in the form of saturated sampling so that the number of samples is 174. Collecting data using a psychological scale with the Likert scale model, namely the achievement motivation scale and the academic flow scale. Data analysis of this research used Pearson Product Moment correlation technique with the help of the SPSS 16.0 for windows program. Based on the results of the correlation analysis, the correlation coefficient rxy = 0.466 (significance 0.000 <0.05) which means that the researcher's hypothesis is accepted, namely there is a positive relationship between achievement motivation and academic flow in students of Muhammadiyah Junior High School 8 Tanggulangin Sidoarjo. The higher the student's achievement motivation, the higher the academic flow. Conversely, the lower the student's achievement motivation, the lower the academic flow. The effect of achievement motivation on academic flow is 19.5%.